BUILDING COMMUNITY POTENTIAL BY INCREASING AWARENESS IN READING IN CIBANTENG VILLAGE, CIAMPEA DISTRICT, BOGOR REGENCY - Triana, Rumba; Hidayat, Muhammad (STAI Al-Hidayah Bogor, 2024)
Indicator of a nation's progress. In Indonesia, although the level of reading interest has begun to increase, when compared with other countries, the reading interest index is still relatively low. Therefore, various efforts are needed to encourage increased public interest in reading. Several parties who must be involved in increasing interest in reading include the government, libraries, librarians and the community. Among all this, libraries have a central role in efforts to increase reading interest. This PkM aims to explore the role of online libraries in villages in supporting education, literacy and community empowerment. Online libraries are identified as digital information centers that can improve access and quality of education in rural areas. Community Service (PkM) activities by the STAI Al Hidayah academic community in Cibanteng Ciampea Bogor village aim to increase empathy, concern and community welfare through their role as problem solvers. , motivator, facilitator and development dynamist. The focus of this PkM is to explore the role of online libraries in supporting education by creating the Village Month or Village Online Books program, to increase literacy and empower the community. The results show that the Village Month or Village Online Books program can improve access and quality of education and digital literacy, and provide important learning resources.